2011
DOI: 10.1016/s0377-1237(11)60053-1
|View full text |Cite
|
Sign up to set email alerts
|

A study of seroprevalence of hepatitis B and hepatitis C among troops in Armed Forces

Abstract: error taken at 5% and expected deviation as 1% for HBV and 0.5% for HCV, a minimum sample size of 1120 for HBV prevalence study and 1521 for HCV prevalence study was obtained. The sample was selected from the study population of army units located in the same station by the method of multistage random sampling.A detailed questionnaire was developed to study the risk factors for transmission of HBV and HCV infections and was administered to all serving personnel during sample collection. RESULTSA total of 1511 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
(4 reference statements)
0
3
1
Order By: Relevance
“… 32 Our finding is higher than reports in Lithuania (1.97%), 33 Pakistan (3.24%; 34 2.8% 35 ), China (0.44%), 36 Greece (0.32%), 37 Caribbean country (4.0%), 38 Brazil (0.22%), 39 UK (0.37%), 40 and India (1.25%). 41 The discrepancy between our findings and the studies conducted elsewhere might be due to variations in sample size, sampling technique, socioeconomic status, availability of medical services, study period, vaccination status, type of risk exposure to HBV infection, and diagnostic techniques.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“… 32 Our finding is higher than reports in Lithuania (1.97%), 33 Pakistan (3.24%; 34 2.8% 35 ), China (0.44%), 36 Greece (0.32%), 37 Caribbean country (4.0%), 38 Brazil (0.22%), 39 UK (0.37%), 40 and India (1.25%). 41 The discrepancy between our findings and the studies conducted elsewhere might be due to variations in sample size, sampling technique, socioeconomic status, availability of medical services, study period, vaccination status, type of risk exposure to HBV infection, and diagnostic techniques.…”
Section: Discussioncontrasting
confidence: 95%
“… 46 , 47 In contrast, no co-infection of these viruses was detected in studies conducted in Ethiopia and elsewhere. 16 , 38 , 41 The absence and/or low prevalence of HBV and HCV co-infection is related to the replication inhibition mechanism of both viruses. A mutual inhibition of viral replication occurs in HBV and HCV co-infection, with HCV exerting a negative effect on HBV replication and HBsAg carriers with concurrent HCV infection having low-level HBV viremia, low titers of HBsAg in serum, and low-levels of intracellular HBsAg.…”
Section: Discussionmentioning
confidence: 99%
“…16 Similarly, a community based cross sectional study in 2011 also found the overall seroprevalence of HBV infection among population of the Indian Armed Forces to be 1.25%. 17 Screening of blood donors from Kolkata has also similarly shown HBsAg seropositivity of 0.99%. 18 One community-based study, however, found a seroprevalence rate of 7.9%.…”
Section: Hepatitis Bmentioning
confidence: 95%
“…The prevalence of HBV infection among the Indian Armed Forces population was 1.25%, according to a study carried out among troops of the armed forces; 19 however, there has been limited information on the prevalence of occult hepatitis B among barbers due to lack of studies on the subject in the armed forces. The current study does not bring out any significant difference in the prevalence of occult hepatitis B in the barbers serving the armed forces clientele and the general population.…”
Section: Armed Forces Scenariomentioning
confidence: 99%